HUBUNGAN KALORI SARAPAN PAGI DENGAN STATUS GIZI MAHASISWA TINGKAT PERTAMA PROGRAM STUDI PENDIDIKAN DOKTER UNIVERSITAS ABDURRAB - Nita Indriani Parna; Yulnefia Yulnefia (LPPM Universitas Abdurrab, 2022)
Various studies have shown that medical students experience more stress than students from other study programs. Students who experience stress lose their appetite so they often skip meals. People who skip breakfast before 9:00 am will tend to be overweight and obese. The aim of this study was to analyze the relationship between breakfast calories and the nutritional status of freshmen medical students at Universitas Abdurrab.This research used an analytic observation study design, with a cross sectional research design. This research was conducted on freshmen of the Abdurrab University medical education program. The results of the research from 40 respondents were that most of the respondents had good nutritional status. The p-value (0.304) > (0.05) indicates that there is no significant relationship between breakfast calories and the nutritional status of the respondents. Therefore, it can be concluded that there is no significant relationship between breakfast calories and freshmen medical students at Universitas Abdurrab.